Studies on the Impact of Ring Seiner Equipped with AIS Transponder Operated Along the Ullal Coast off Mangaluru - Prapti; Naik, Jaya; Varadaraju, S.; Badami, Shashidhar H.; Mendon, Jayaprakash; Annappaswamy, T. S.; Atnur, Vijay S. (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted over a period of nine months from December, 2023 to August, 2024 along the Ullal coast off Mangaluru, Karnataka, to assess the role of Automatic Identification System (AIS) technology in enhancing the efficiency and sustainability of Ring seine fishing. The study focused on species composition, fuel efficiency, and operational performance. A 468-meter-long Ring seine net, operated with a 40 HP outboard engine, was deployed fortnightly at a depth of 12 meters, resulting in a total catch of 37,426.9 kg. The highest catches were recorded during the monsoon months (June to August), with a peak catch of 5,530 kg on the 255th day. The integration of AIS technology significantly improved fishing precision by enabling the fishers to locate the fish shoals quickly, thereby optimizing the fuel use and reducing unproductive efforts. Statistical analysis confirmed that the AIS-assisted operations yielded significantly higher catch rates and better fuel efficiency (p < 0.05) compared to the traditional methods. Economically, the AIS-supported system reduced operational costs and ensured equitable income distribution among the crew members through a share system. Additionally, AIS contributed to sustainable fishing by enhancing target species selectivity and minimizing bycatch. The study concluded that the adoption of AIS technology in Ring seine fishing improved productivity and cost-efficiency, while supporting small-scale fishers’ livelihoods and promoting responsible marine resource management.